2017
DOI: 10.1111/evj.12739
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of pregnancy after embryo transfer is reduced in recipient mares with a short preceding oestrus

Abstract: The likelihood of pregnancy in recipient mares is positively correlated with the duration of endometrial oedema during the oestrus preceding ET. This suggests a role for an adequate duration of oestrogenic priming during oestrus on uterine receptivity and embryo survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
4
27
1
Order By: Relevance
“…This previous study also demonstrated that only mares showing uterine edema ≥2 (similar to the grading used herein) became pregnant (Souza et al, 2015). Again, this finding is consistent with the Utrecht's study demonstrating that duration of uterine edema is important for normal pregnancy rates in embryo transfer recipient mares (Cuervo-Arango et al, 2017). In the present study, recipients mares with a fresh ovulation (< 5 days) had improved uterine features scores when a second dose of prostaglandin F2α was given (G8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This previous study also demonstrated that only mares showing uterine edema ≥2 (similar to the grading used herein) became pregnant (Souza et al, 2015). Again, this finding is consistent with the Utrecht's study demonstrating that duration of uterine edema is important for normal pregnancy rates in embryo transfer recipient mares (Cuervo-Arango et al, 2017). In the present study, recipients mares with a fresh ovulation (< 5 days) had improved uterine features scores when a second dose of prostaglandin F2α was given (G8).…”
Section: Discussionsupporting
confidence: 92%
“…Though, mares with fresh ovulation (< 5 days) receiving one dose of prostaglandin (G7) had lower uterine edema scores during estrogen treatment and had remarkably lower conception rates compared with other groups. A recent study out of the Netherlands, demonstrated that pregnancy rate is positively correlated with the duration of uterine edema during estrous prior to the embryo transfer (Cuervo-Arango et al, 2017). Our findings in hormonally manipulated embryo recipient mares supports the claim by the Dutch group that showed that uterine edema is important for normal establishment of pregnancy in embryo recipient mares.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The work presented in the papers of Ortiz-Escribano et al [1] and of Perez Marin et al [2] had been granted ethical approval in accordance with the policies of the local institutions, and of this journal. Nonetheless, these papers provide examples of 1) embryos being deliberately sacrificed for experimental purposes and 2) embryos being transferred using techniques which have a significantly lower survival rate than that usually achieved following transfer of in vivo produced embryos which have not been cryopreserved [3,13]. Notwithstanding the fact that the law seems to offer no protection to equine embryos per se, this gives one pause for thought about whether loss of or damage to them should nonetheless be a cause for ethical concern.…”
Section: Legal Protections Of Animal Embryosmentioning
confidence: 99%
“…Two papers are published in this issue of Equine Veterinary Journal which involve the production of equine embryos using cryopreservation of either oocytes or embryos [1,2] whilst a third examines outcomes achieved in embryo transfer in clinical practice [3] and a fourth reports in vivo experiments addressing placental adaptions to fetal growth [4]. Equine embryos are defined as being less than 42 days of gestational age.…”
mentioning
confidence: 99%